Sensorineural hearing loss in chronic otitis media: analysis of an overlooked entity! - Shetty, Kishore C.; Jayaramaiah, Samatha K.; Kolathingal, Biniyam; Alva, Shravan (International Journal of Otorhinolaryngology and Head and Neck Surgery, 2019)
Background: In developing countries, hearing loss continues to be the major public health problem. Among the various causes of hearing loss, chronic otitis media (COM) is one of the commonest. In COM, the presence of sensorineural hearing loss is well established. Our study intends to determine the prevalence of sensorineural hearing loss in chronic otitis media. Methods: This was a cross sectional descriptive study of 151 subjects between the age group of 10 and 60 years. Patients having unilateral chronic otitis media of both mucosal and squamosal types were selected. All patients were evaluated clinically and audiologically. The type, duration of disease and type of perforation is correlated with degree of sensorineural hearing loss. Interaural differences in bone conduction thresholds at 500 Hz, 1 kHz, 2 kHz and 4 kHz were also noted. Results: A statistically significant correlation was noted between type of disease and perforation with hearing loss. A significant interaural difference was noted across the speech frequencies. Sensorineural hearing loss of 19.1% was seen. Conclusions: Significant sensorineural hearing loss is seen in chronic otitis media which was greater in squamosal disease. Statistically significant correlation was noted between type of disease and type of perforation with hearing loss.